Public Transportation Sector Improvement Policy Strategy in Jambi City Towards Net Zero Emissions - Defrizal Defrizal (Jurnal Impresi Indonesia, 2025)
This research emphasizes the urgency of balancing judicial independence with accountability, given the persistent gaps within Indonesia’s judicial system. Weak integrity, legal voids regarding judicial responsibility, and inadequate accountability mechanisms have fostered feudalism, inconsistency in rulings, and deteriorating decision quality, thereby creating accountability loopholes. The study reconceptualizes negligence (culpa lata) into two forms: negligence leading to corruption, collusion, and nepotism (KKN), and non-KKN negligence. The first category, analyzed through Rational Choice Theory, Opportunity Theory, and White-Collar Crime Theory, identifies common patterns of misconduct such as neglecting evidence, manipulating facts, and falsifying verdicts. The second category, non-KKN negligence, is divided into two phases: individual-level negligence assessed through Social Control Theory (F. Ivan Nye, supported by Jackson Toby), and institutional-level failures examined through Sociological Institutionalism and Neo-Institutional Rational Choice. Empirical validation is provided through the Ronald Tannur verdict (KKN-related negligence) and the Fikri et al. case (non-KKN negligence), which expose the inadequacy of current ethical and administrative supervisory mechanisms. To address these gaps and restore public trust, the study proposes the criminalization of culpa lata as a last resort. This concept integrates a merit-based system and Artificial Intelligence (AI) with Natural Language Processing (NLP) to evaluate rulings and detect negligence. Cases identified are processed through a specialized court named Privilegiatum Termodifikasi. This framework seeks to enforce judicial accountability without undermining judicial independence, applying strict sanctions to reduce legal errors and strengthen public confidence in Indonesia’s judicial system.